The coalescence and etching of metal nanostructures via solution approach - Tan, Rachel Lee Siew (2016)
This thesis summarizes my research studies on the coalescence and etching of nanomaterials. This thesis consists of two parts: (1) coalescence, aggregation and encapsulation of nanoparticles and its application on screening of synergistic effects and (2) coalescence and etching of silver nanowires. For the first part, we make use of the coalescence of different nanoparticles to create bimetallic junctions between nanoparticles for screening of synergistic effects in catalytic reaction (Chapter 2). As this screening method involves the aggregation of nanoparticles to create bimetallic regions, we studied how to have controlled aggregation without additional reagents in Chapter 3. For the second part, we studied how we can make use of chemically induced ripening of silver nanowire junctions to reduce the sheet resistance of silver nanowire network (Chapter 4). In addition, we also studied how breaking of symmetry during etching of silver nanowires can yield unique nanowire structures (Chapter 5).